What’s in a Debt Letter? A Content and Linguistic Analysis of Student Loan Debt Letters (Higher Education Politics and Economics, 2021)
Since 2012, many Title IV institutions of higher education have sent their students debt letters to inform these students of their outstanding loan amounts, estimated or real monthly payments, and other loan-related information. This study analyzes a sample of 24 debt letters gathered from institutions of higher education across the country. Results suggest most debt letters are not readable by the average first- or second-year college student, jargon differs between sectors (ex: public, private), and debt letters share many common elements, such as aggregate loan totals and interest rates, but many do not include contact information or any multimedia, even though letters were written to be delivered digitally. Implications for research, practice, and financial aid communication are addressed.